Experimental Study on Mechanical Properties of Gas Storage Sandstone and Its Damage Under Temperature and Pressure - Wang, Xiaoping; Wang, Lehua; Zhao, Baoyun; Wu, Yingjie; Yang, Jiaosheng; Sun, Junchang (Frontiers in Earth Science, 2022)
With the ever-increasing demand for energy, energy mining is developing in the deep underground. In this paper, a conventional triaxial test and a triaxial test at different temperatures (45 MPa confining pressure) have been carried out for sandstone in Hutubi gas storage, and the mechanical properties of the sandstone at different temperatures are analyzed. Based on the damage theory, the damaged relationship of sandstone under thermal-mechanical coupling is deduced, and the damage evolution law of sandstone in gas storage is analyzed. The results show that: 1) In the conventional triaxial test, as the confining pressure increases, the peak strength and elastic modulus of the sandstone are higher, and the specimen is partially sheared and damaged. 2) In the triaxial test under the effect of temperature, the peak strength of the sample decreases with the increase of temperature. Compared with the four stages of the conventional triaxial test, the stress-strain curve adds a ductility stage. The failure mode of the sample is mainly micro-cracks extended ductile destruction. 3) Under the thermal-mechanical coupling of sandstone, the higher the test temperature, the greater the initial damage of the sample. With the joint action of axial force and temperature, the damage of specimen becomes more obvious. This research results can provide the experimental basis and mechanism understanding for the analysis of mechanical properties of gas storage sandstone and the application of deep underground engineering.